Rabies Virus Infection Induces Microtubule Depolymerization to Facilitate Viral RNA Synthesis by Upregulating HDAC6 - Zan, Jie; Liu, Song; Sun, Dong-Nan; Mo, Kai-Kun; Yan, Yan; Liu, Juan; Hu, Bo-Li; Gu, Jin-Yan; Liao, Min; Zhou, Ji-Yong (Frontiers in Cellular and Infection Microbiology, 2017)
ABSTRACT Rabies virus (RABV) is the cause of rabies, and is associated with severe neurological symptoms, high mortality rate, and a serious threat to human health. Although cellular tubulin has recently been identified to be incorporated into RABV particles, the effects of RABV infection on the microtubule cytoskeleton remain poorly understood. In this study, we show that RABV infection induces microtubule depolymerization as observed by confocal microscopy, which is closely associated with the formation of the filamentous network of the RABV M protein. Depolymerization of microtubules significantly increases viral RNA synthesis, while the polymerization of microtubules notably inhibits viral RNA synthesis and prevents the viral M protein from inducing the formation of the filamentous network. Furthermore, the histone deacetylase 6 (HDAC6) expression level progressively increases during RABV infection, and the inhibition of HDAC6 deacetylase activity significantly decreases viral RNA synthesis. In addition, the expression of viral M protein alone was found to significantly upregulate HDAC6 expression, leading to a substantial reduction in its substrate, acetylated α-tubulin, eventually resulting in microtubule depolymerization. These results demonstrate that HDAC6 plays a positive role in viral transcription and replication by inducing microtubule depolymerization during RABV infection.